2014
DOI: 10.1128/aac.02437-14
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal Weight Gain and Gut Microbiota Modifications Are Side Effects of Long-Term Doxycycline and Hydroxychloroquine Treatment

Abstract: b Doxycycline has been proposed for the treatment of malnourished children in developing countries, and its use has been associated with weight gain in healthy volunteers. No previous studies have assessed abnormal weight gain as a putative side effect of long-term doxycycline treatment; thus, the objective of the present study was to characterize this phenomenon. We also analyzed the role of the gut microbiota in this effect. We assessed changes in the body mass index in Q fever endocarditis patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 34 publications
5
84
0
5
Order By: Relevance
“…Auwerx and colleagues (Chatzispyrou et al 2015;Moullan et al 2015) demonstrated that doxycycline negatively impacts mitochrondrial function. Doxycycline can also impact the gut microbiota in humans; the direct impact of this on adipose biology is unclear but potentially significant (Angelakis et al 2014). Furthermore, doxycycline can regulate the function of matrix metalloproteinases (Stechmiller et al 2010).…”
Section: Perspectives Limitations and Future Directionsmentioning
confidence: 99%
“…Auwerx and colleagues (Chatzispyrou et al 2015;Moullan et al 2015) demonstrated that doxycycline negatively impacts mitochrondrial function. Doxycycline can also impact the gut microbiota in humans; the direct impact of this on adipose biology is unclear but potentially significant (Angelakis et al 2014). Furthermore, doxycycline can regulate the function of matrix metalloproteinases (Stechmiller et al 2010).…”
Section: Perspectives Limitations and Future Directionsmentioning
confidence: 99%
“…Although doxycycline is prescribed long term for conditions ranging from acne to malaria, while generally safe, its prolonged use has been rarely associated with irritable bowel syndrome, abnormal weight gain and photosensitivity. [34][35][36] Currently, a few laboratories are researching vaccines to prevent bacterial STIs. While no vaccine is imminent, continued research may generate a product for further evaluation.…”
Section: Novel Approaches To Sti Prevention In Msmmentioning
confidence: 99%
“…Twenty-eight mice (>50 wk) were divided in WT males (WTM), WT females (WTF) knockout males (KOM), and knockout females (KOF). All of them were treated with doxycycline to avoid differences caused by the antibiotic because it has been proven that doxycycline administration not only alters the microbiota composition [203] it also significantly modifies the expression of important cellular pathways [204]. A month after completing the doxycycline treatment, fresh stool was obtained from each animal in a noninvasive way and analyzed by real-time PCR with specific primers for the 4 most dominant orders of gut bacteria: Enterobacteriales, Lactobacillales, Bacteroidales, and Clostridiales [205].…”
Section: Lack Of Am Results In Changes In Gut Microbiotamentioning
confidence: 99%